The Determinants of Academic Resilience among Undergraduate Students Post COVID-19 - Daulay, Nurussakinah (Universitas Islam Indonesia, 2024)
This study examines the determinants of students academic resilience, particularly the impact of social support and gratitude in the aftermath of the COVID-19 pandemic. A total of 240 students were selected as participants, with data collected through surveys by distributing online questionnaires. The instruments adopted were the Multidimensional Scale of Perceived Social Support, The Gratitude Questionnaire-6, and the Academic Resilience Scale. Furthermore, the data collected were analyzed using multiple regression and path analysis. The results showed that: 1) social support did not influence gratitude (F(1,238) = .488, p = .485; p>0.01) and academic resilience (F(1,238) = .568, p = .452; p>0.01), 2) gratitude had a significant impact on academic resilience (F(1,238) = 6.854, p = .009; p<0.01). Despite reduced social support from parents, lecturers, and the community during the pandemic, internal protective factors proved instrumental in navigating challenging circumstances and fostering the cultivation of academic resilience.